2019
DOI: 10.1371/journal.pntd.0007479
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the value of targeted versus area-wide mosquito control scenarios to limit arbovirus transmission with human mobility patterns based on different tropical urban population centers

Abstract: Vector control is still our primary intervention for both prevention and mitigation of epidemics of many vector-borne diseases. Efficiently targeting control measures is important since control can involve substantial economic costs. Targeting is not always straightforward, as transmission of vector-borne diseases is affected by various types of host movement. Here we assess how taking daily commuting patterns into consideration can help improve vector control efforts. We examine three tropical urban centers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Quantifying mosquito dispersal of both wild-type and introduced mosquito strains in any given landscape is, therefore, critical for the considerations of the size of the treatment area and the surrounding buffer zones. Those considerations complement practical operational deliberations of the availability of human and economic resources for implementation and the sample sizes required to capture epidemiological endpoints [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying mosquito dispersal of both wild-type and introduced mosquito strains in any given landscape is, therefore, critical for the considerations of the size of the treatment area and the surrounding buffer zones. Those considerations complement practical operational deliberations of the availability of human and economic resources for implementation and the sample sizes required to capture epidemiological endpoints [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vector control is of great importance in preventing and mitigating dengue burden [ 10 , 11 ]. A previous study conducted in Sri Lanka revealed that mosquito vector density could be a mediator of intensified dengue control measures and dengue incidence [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The experience in Guangzhou, especially the effective integrated intervention strategy with the cross-departmental collaboration and supervision from senior officials could also be beneficial for other locations with dengue epidemics. Vector control is of great importance in preventing and mitigating dengue burden [10,11]. A previous study conducted in Sri Lanka revealed that mosquito vector density could be a mediator of intensified dengue control measures and dengue incidence [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mosquitoes only fly short distances and usually remain near where they hatched [5], [6], [7], [8], human movement is a key component of vector-borne epidemiology [9]. In particular, transmission is influenced by social connections and the transport system [10], [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%